The Adaptive Evolution and Gigantism Mechanisms of the Hadal “Supergiant” Amphipod Alicella gigantea - Li, Wenhao; Wang, Faxiang; Jiang, Shouwen; Pan, Binbin; Chan, Jiulin; Xu, Qianghua (Frontiers in Marine Science, 2021)
Hadal trenches are commonly referred to as the deepest areas in the ocean and are characterized by extreme environmental conditions such as high hydrostatic pressures and very limited food supplies. Amphipods are considered the dominant scavengers in the hadal food web. Alicella gigantea is the largest hadal amphipod and, as such, has attracted a lot of attention. However, the adaptive evolution and gigantism mechanisms of the hadal “supergiant” remain unknown. In this study, the whole-body transcriptome analysis was conducted regarding the two hadal amphipods, one being the largest sized species A. gigantea from the New Britain Trench and another the small-sized species Bathycallisoma schellenbergi from the Marceau Trench. The size and weight measurement of the two hadal amphipods revealed that the growth of A. gigantea was comparatively much faster than that of B. schellenbergi. Phylogenetic analyses showed that A. gigantea and B. schellenbergi were clustered into a Lysianassoidea clade, and were distinct from the Gammaroidea consisting of shallow-water Gammarus species. Codon substitution analyses revealed that “response to starvation,” “glycerolipid metabolism,” and “meiosis” pathways were enriched among the positively selected genes (PSGs) of the two hadal amphipods, suggesting that hadal amphipods are subjected to intense food shortage and the pathways are the main adaptation strategies to survive in the hadal environment. To elucidate the mechanisms underlying the gigantism of A. gigantea, small-sized amphipods were used as the background for evolutionary analysis, we found the seven PSGs that were ultimately related to growth and proliferation. In addition, the evolutionary rate of the gene ontology (GO) term “growth regulation” was significantly higher in A. gigantea than in small-sized amphipods. By combining, those points might be the possible gigantism mechanisms of the hadal “supergiant” A. gigantea.